A study of mantle inclusions in the Koffiefontein Kimberlite pipe, South Africa - CARDOSO_P (Department of Chemistry, 2023)
Mantle derived rock and mineral fragments from the Koffiefontein Kimberlite Pipe have been studied in the form of xenoliths, megacrysts, concentrate minerals and inclusions in diamonds. Mantle derived xenoliths are unusuaLly scarce. The predominant xenoliths are pyroxenites. Peridotites are rare and eclogites are very rare. The pyroxenites have been assigned to five categories. In general, they show a clear metamorphic textural history with widespread evidence of exsolution, polygonisation and deformation. Some of these pyroxenites are interpreted to represent the crystallisation products of basaltic magma at depth. Some have been metasomatised. The pyroxene chemistries suggest that more than one pyroxenite body has been sampled. The peridotites are very similar to the common peridotites of N. Lesotho and are thought to represent depleted mantle. The Koffiefontein diamonds contain both eclogitic and peridotitic inclusions. The inclusions show evidence for lack of equilibration, and one appears to link tog~ther the two parageneses mentioned above. The presence of (MgFe)O as an inclusion is reported. The megacrysts studied consisted only of garnets, and a few pyroxenes. They are interpreted to have crystallised from a magma which cooled slowly and was relatively deficient in Tio2 to account for the scarcity of ilmenite. The heavy mineral concentrate contained garnet, orthopyroxene, opaque minerals and clinopyroxene in order of abundance. The opaque minerals were chromite and ilmenite. The chemical compositions of most of the concentrate grains do not match the mineral compositions found in xenolith s, or megacrysts. A small number of concentrate grains have compositions ma tched by the diamond inclusions. Attempts to a pply geothe r mobarometry to the pyroxenites and to the diamond inclusions gave conflicting results which areascribe d to lack of equilibration between co-existing mineral phases and/or within individual mineral grains. The Koffiefontein xenolith suite is unusual for the relative abundance of pyroxenite and the scarcity of peridotite. The concentrate is unusual for the relative abundance of orthopyroxene particularly and of chromi te.